Profiling the dynamics of abscisic acid and ABA-glucose ester after using the glucosyltransferase UGT71C5 to mediate abscisic acid homeostasis in Arabidopsis thaliana by HPLCâESI-MS/MS - Dong-Mei Xiong; Zhen Liu; Han Chen; Jin-Tao Xue; Yi Yang; Cong Chen; Li-Ming Ye (Elsevier, 2014)
The HPLCâMS/MS method was developed to profile the dynamics of abscisic acid (ABA) and ABA-glucose ester (ABA-GE) after cloning glycosyltransferase enzyme family gene AtUGT71C5 into Arabidopsis thaliana. By constructing over-expression lines (OE) and down-expression lines (DN), we acquired mutant strains to analyze the function of AtUGT71C5. The multiple-reaction monitoring (MRM) was used for quantitative determination in negative mode. The transition was m/z 263.1â153.0 for ABA ([MâH]+), m/z 425.1â263.0 for ABA-GE ([MâH]+), and m/z 321.0â152.0 for chloramphenicol. The linear range was 0.8684â217.1Â ng/mL for ABA and 0.3920â196.0Â ng/mL for ABA-GE. The accuracy was 88.0â109.0% for ABA and 86.6â113.0% for ABA-GE; the inter-day and intra-day precisions were less than 5.4% for ABA and 8.9% for ABA-GE, respectively. This method is simple and sensitive enough for determination of ABA and ABA-GE in A. thaliana leaves. All the evidence confirmed the speculation that AtUGT71C5 can mediate abscisic acid homeostasis. Keywords: HPLCâMS/MS, ABA, ABA-GE, AtUGT71C5